(untitled) (Research, Society and Development, 2020)
Mathematics has the principle of understanding and giving meaning to things, allowing man to solve problems of daily life, thus functioning as an essential instrument for the construction of knowledge in other areas. However, many students have difficulty learning mathematical concepts and their low performance in this discipline. This work investigated how the teaching of Mathematics has been conducted - methodologies practiced in the classroom, the learning difficulties of students in assimilating content and of teachers in promoting teaching - thus identifying the main problems that affect teaching and learning of this curricular component. The data were obtained from semi-structured questionnaires applied to teachers and students of the 3rd grade of high school. It was found that teachers are aware of the barriers of this process and cited as the main difficulties the lack of prior knowledge, indiscipline and lack of interest of students; insufficient educational resources and precarious school structure; lack of continued training and extensive workload for teachers, which make it difficult to plan and prepare classes that meet the needs of students. Despite showing to know the importance of learning mathematics, the students claimed that these contents are difficult to assimilate, lack of context in the approach and that they do not master prerequisites and lack of time for studies. The main suggestions of teachers to minimize this problem consider the provision of appropriate teaching resources, investment in the infrastructure of school units and incentives for teachers. The students consider that working with mathematical content together with other subjects would facilitate the learning of abstract concepts.